Determinant Factors of Food Security in Indonesia - Arif Wahyu Widada; Masyhuri Masyhuri; Jangkung Handoyo Mulyo (Agro Ekonomi, 2017)
All countries around the world are dealing the same problem in assuring the sufficiency of food for feeding their people. Indonesia is the biggest agrarian state in South East Asia and the fourth largest state in the world. The challenge faced by Indonesia with a large population is on how food meets the needs of its population, which until now Indonesia has not been able to guarantee the fulfillment of food supply for its population. This study aims to analyze the influence of determinant factors toward Indonesian food security. Binary Logit Model was employed to analyze determinant factors of Indonesian food security. Jonsson and Toole criterion of food security was used to identify Indonesian food security status as dependent variable. This research found that land area, rice production, corn production, soybean production, chicken meat production, beef production, the population density the CPI (Customer Price Index) including the CPI for housing, electricity and gas, the CPI for health, the CPI for transportation and financial services, and FIMI (Food Insecurity Multidimensional Index) have significant influences towards the level of food security in Indonesia. It means that food security could be achieved by not only improving the quantity and quality of consumption, but also improving food supply, the ability to access economically and the stability.